Analisis Manajemen Waktu Organisasi dan Kuliah Aktivis Mahasiswa Program Studi Pendidikan Matematika Universitas Muhammadiyah Surakarta (Jurusan Matematika FMIPA UNNES, 2016)
The purpose of this study is to describe time management of student activist of mathematics education of Muhammadiyah University of Surakarta. The data of study is collected by observation, questionnaires, interviews, and documentation. Data are analyzed interactively by 4 methods: collecting data, data reduction, data display, and draw conclusions. The results show that (1) Time management of organization of student activist take priority to the work program rather than regular meetings. Students spend time for organization after the dismissal class. Student activist spend the spare time for organization’s matter effectively and efficiently. The student-activist face difficulty in managing time while they are invited to play with friends, or getting into attached to social media. (2) Time management of study of student-activist take priority to be presence 75% for classes as the requirement to join the final test. They solve the crushed-schedule of classes by joining the other class schedule.Assignments is done while they have a spare time by having discussion with friends. The academic achievement of student-activist can be categorized as satisfied category. This research find that student-activist whose long in pursue undergraduate program approximately takes 18 sks/semester